Effects of situational simulation and online first-aid training programs for nurses in general medical wards: A prospective study. (January 2021) - Hsieh, Pei-Yin; Lin, Hsin-Yi; Chang, Chin-Hao; Chang, Yu-Chuan; Cheng, Hui-Ping; Wang, Chun-Yeuh; Wang, Min-Ling; Wang, Huey-Jiuan; Liu, Hui-Ting; Chen, Jin-Shing; Hsiao, Fei-Hsiu
Abstract: Background: To maintain patient safety, effective first-aid skills are necessary during emergencies. It is important to develop in-service education programs to equip clinical nurses with first-aid skills. Objectives: This study explored the effects of first-aid skills and knowledge between situational simulation training and online teaching. It also examined the different effects of two training programs associated with nurses' baseline first-aid ability. Design: This was a randomized, single-blind controlled study. Setting: The study was conducted from December 15, 2016 to May 28, 2018, in the nursing department of a medical center in Taiwan. Participants: Participants were 92 general ward nurses. Methods: Participants were randomly assigned to either a situational simulation training or an online teaching group. We used a first-aid knowledge test (FAKT) and a first-aid skills test (FAST) to measure the participants' learning outcomes after intervention and we did cost comparisons between groups. Results: There were no significant differences in the changes in FAKT and FAST scores after intervention between situational simulation training and online teaching groups ( p  = 0.76, p  = 0.45). All the participants in both training programs showed improvements via increased scores on FAST ( M  ±  SD  = 35.27 ± 12.08 for online teaching, M  ±  SD  = 36.08 ± 10.78 for situational simulation training) and FAKT ( M  ±  SD  = 21.09 ± 18.59 for online teaching, M  ±  SD  = 23.39 ± 15.36 for situational simulation training). However, for the subgroup of participants who scored <75% on the FAST pretest, better improvements only occurred in the situational simulation training, but the situational simulation training program had higher costs than the online teaching program. Conclusions: The improvement was greater in the situational simulation training group among nurses who could not exceed scores of 75% for first-aid skills. First-aid skill scores below 75% are likely a sign of nurses who need more assistance, discussion, and debriefing from situational simulation training.